Ethics in Social Research: challenges to the biomedical model - DOI: 10.3395/reciis.v2.Sup1.211en - Debora Diniz; Iara Guerreiro (Instituto de Comunicação e Informação Científica e Tecnológica em Saúde (Icict) da Fundação Oswaldo Cruz (Fiocruz), 2008)
This article analyzes the main challenges involved in the ethical review of social research projects that use qualitative techniques for gathering data. The Brazilian ethical review system was constructed having biomedical sciences as the main reference. This article goes over some of the main points of ethical tension in social research by discussing five classic cases in human and social sciences. It supports the possibility of social research being included in the current ethical review system, as long as there is a sensitization of the ethics committees regarding the methodological particularities imposed by qualitative techniques. Finally, the need for specific ethical guidelines for social research is also considered.